Characterization of the PRODUCTION of ANTHOCYANIN PIGMENT 1 Arabidopsis dominant mutant using DLEMMA dual isotope labeling approach. (June 2021) - Dong, Yonghui; Feldberg, Liron; Rogachev, Ilana; Aharoni, Asaph
Abstract: Stable isotope labeling has emerged as a valuable tool for metabolite identification and quantification. In this study, we employed DLEMMA, a dual stable isotope labeling approach to identify and track phenylpropanoid pathway in Arabidopsis thaliana . Three forms of phenylalanine (Phe), including unlabeled, Phe 13 C6 and Phe 13 C6 2 H5, were used as feeding precursors. The unique isotopic pattern obtained from MS spectra significantly simplified data processing and facilitated global mining of Phe-derived metabolites. Following this approach, we have identified 35 phenylalanine-derived metabolites with high confidence. We next compared phenylpropanoids contents between leaves of wild type (WT) and the dominant PRODUCTION OF ANTHOCYANIN PIGMENT 1 (pap1-D) Arabidopsis thaliana mutant using a combined sample matrices and label-swap approach. This approach was designed to correct any unequal matrix effects between the two divergent samples, and any possible uneven label incorporation efficiency between the two differently labeled Phe precursors. Thirty of the 35 identified metabolites were found differential between WT and pap1-D leaves. Our results shown that the ectopic PAP1 expression led to significant accumulation of cyanidin-type anthocyanins, quercetin-type flavonols and hydroxycinnamic acids and their glycosylated derivatives. While levels of kaempferol glycosides and a hydroxycinnamic acid amide were reduced in the pap1-D leaves. Graphical abstract: Image 1 Highlights: A dual stable isotope labeling approach is used to track phenylpropanoid pathway. Metabolite labeling patterns allows for high-confidence metabolite identification. Labeling efficiency can be used to estimate metabolite location in the pathway. A combined sample matrices and label-swap approach is used for relative comparison.